2018
DOI: 10.1002/prot.25642
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of cysteine exposure and global protein dynamics in small‐molecule recognition by a regulator of G‐protein signaling protein

Abstract: Regulator of G protein signaling (RGS) proteins play a pivotal role in regulation of G proteincoupled receptor (GPCR) signaling and are therefore becoming an increasingly important therapeutic target. Recently discovered thiadiazolidinone (TDZD) compounds that target cysteine residues have shown different levels of specificities and potencies for the RGS4 protein, thereby suggesting intrinsic differences in dynamics of this protein upon binding of these compounds. In this work, we investigated using atomistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…On the basis of this work, we have a preliminary understanding of the influence of the charge-characteristic of Ca-montmorillonite on water molecules and Ca 2+ . In the future, we will conduct an in-depth study on the influence mechanism of the charge density of Ca-montmorillonite on the polarity of the Si–O surface [43]. In addition, we will further study the structure, performance, and application characteristics of organo-modified montmorillonite by means of MD.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of this work, we have a preliminary understanding of the influence of the charge-characteristic of Ca-montmorillonite on water molecules and Ca 2+ . In the future, we will conduct an in-depth study on the influence mechanism of the charge density of Ca-montmorillonite on the polarity of the Si–O surface [43]. In addition, we will further study the structure, performance, and application characteristics of organo-modified montmorillonite by means of MD.…”
Section: Discussionmentioning
confidence: 99%
“…The salt-bridging interaction analysis was carried out using VMD based on a distance criterion uniformly applied to determine the existence of salt-bridges for each frame in all trajectories [54]. Specifically, the formation of a salt-bridging interaction was considered if the distance between any of the oxygen atoms of acidic residues and the nitrogen atoms of basic residues were within a cut-off distance of 3.2 Å.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, using molecular dynamics (MD) simulations we found that RGS19 is more flexible than RGS4 and RGS8 (Shaw et al, 2018). In these modeling studies, we also found that salt bridge interactions were perturbed in response to inhibitor binding (Mohammadi et al, 2019). In this work, we sought to identify residue interactions responsible for flexibility differences among these isoforms and we predicted mutations that alter salt bridge interactions will both enhance RGS protein flexibility and increase the potency of RGS inhibitors such as 4-[(4-fluorophenyl)methyl]-2-(4methylphenyl)-1,2,4-thiadiazolidine-3,5-dione (CCG-50014).…”
Section: Introductionmentioning
confidence: 76%